SAT-LB100 Central and Peripheral Endocannabinoid Levels in Obese Versus Lean Women - Farage-Martins, Mariana (J Endocr Soc, 2020)
The endocannabinoid system (ECS) is thought to be involved in obesity because its activation increases appetite and weight gain (Pagotto et al 2006). The ECS is hyperactivated in the hypothalamus of obese mice, and peripheral overactivation has been observed in humans; circulating 2-arachidonoyl glycerol (2-AG) levels positively correlated with body fat, visceral fat and fasting glucose (Osei-Hyiaman et al 2005) (Bluher et al 2006) (Motaghedi and McGraw 2008) (Cavuoto et al 2007) (Artmann et al 2008) (Bermudez-Silva 2009). The aim of this study was to evaluate whether differential activation of the peripheral versus the central ECS occurred in humans and to test the hypothesis that the ECS is hyperactivated in the human central nervous system (CNS).Cerebral spinal fluid (CSF) and blood samples were collected from 13 obese and 11 lean control women to measure 2-AG and anandamide (AEA) levels.AEA levels were higher in the plasma of obese women (obese: 4.03 ± 0.91 pmol/mL, N=13; lean: 1.84 ± 0.21 pmol/mL, N=10; p<0.05) but were lower in the CSF of obese women. The plasma/CSF ratio was 41.58 ± 5.78 (N=10) in lean women and 103.0 ± 37.36 (N=6) in obese women (p=0.054). There were no correlations between plasma and CSF AEA levels or with any biochemical parameter. The 2-AG analysis was not possible because of technical problems.Our data suggested that in human obesity, the peripheral ECS may be more active than the central ECS. Indeed, the system appeared to be suppressed in the CNS of obese women. Therefore, the peripheral activation of the ECS may be more relevant for obesity. Keywords: Anandamide, 2-arachidonoyl glycerol, obesity, endocannabinoid, endocannabinoid system, cb1 receptor.